WORK POSTURE AND MUSCULOSKELETAL DISORDERS OF COCONUT PEELER WORKERS IN SEI APUNG VILLAGE, ASAHAN REGENCY - Putra Apriadi Siregar; Muchliza Rizwany; Nurhayati Nurhayati (Poltekkes Kemenkes Semarang, 2020)
Posture and certain activities towards work equipment have the potential to cause health problems, even disease. One disease that is identical to workers who have problems with posture is musculoskeletal disorders. This research has a purpose of analyzing the relationship between work posture with musculoskeletal disorders of coconut peeler workers. This research has quantitative research with cross-sectional design. The sample of this research was 52 workers with purposive sampling technique. The data obtained by observation and interviews used Rapid Entire Body Assessment (REBA) and Nordic Body Map (NBM) questionnaire. The analysis relationship used Spearman Rho correlation test with a significance level of 95% (α=0,05). Based on the result of the studied show working period of 1 to 5 years as 33 people (63.5%), work postures is more spread over the value 3 (high category) as 34 people (65.4%), musculoskeletal disorders was mostly in the moderate as 31 people (59.6%). A significant relationship between work posture with musculoskeletal disorders (r=0.534). As a suggestion to take a break or stretching muscles, add hand braces or elbows to prevent the risk of complaints, and to modify the seat to reduce the risk of complaints in the lower back area.